REVERSIBLE COVALENT BINDING INHIBITOR FOR TREATING OR PREVENTING VIRAL INFECTION - KAWANISHI, Eiji; OJIDA, Akio (2023)
The present invention provides a compound for treating or preventing a viral infection.　The present invention pertains to a compound represented by formula (1) [wherein: R1 is a group represented by formula (AA); Y is a group represented by formula (BB); and X is a covalent substituent represented by formula (CC)], a pharmaceutically acceptable salt or solvate thereof, or a prodrug of the same. La présente invention concerne un composé pour le traitement ou la prévention d'une infection virale.　La présente invention concerne un composé représenté par la formule (1) [dans laquelle : R1 est un groupe représenté par la formule (AA) ; Y est un groupe représenté par la formule (BB) ; et X est un substituant covalent représenté par la formule (CC)], un sel ou solvate pharmaceutiquement acceptable de celui-ci, ou un promédicament de celui-ci. 本発明は、ウイルス感染症を処置または予防するための化合物を提供する。　本発明は、式（１）：［式中、R1は、式：（AA）で示される基であり、Yは、式（BB）で示される基であり、Xは、式：（CC）で示されるコバレント置換基である］で示される化合物、またはその製薬的に許容できる塩もしくは溶媒和物、またはそのプロドラッグに関する。